Rol del profesor en el proceso de enseñanza aprendizaje de la investigación en estudiantes de Enfermería de la Universidad de Antioquia, Colombia (2008)
ABSTRACT: to describe the teacher´s role in the research and teaching-learning process among undergraduate nursing students at the University of Antioquia. Methodology: a qualitative study was carried out with an ethnographic focused approach, through two basic inputs: documentary subject related sources and testimonials from two teachers and six students achieved through observation and interviews. The research and teaching-learning process in the school of nursing was captured in detail. Results and Discussion: it was found that when the teachers’ explanations were through and comprehensive the students had more and better information enabling them to acquire skills in project implementation. On the contrary passive attitudes led to lesser participation. The teachers´ role based in his professional expertise promoted interest in research among the students. Conclusion: always a definite didactic strategy favours the acquisition of information and content but not of learning. Recommendations: innovative and creative researcher-teachers are a role model leading the students to become researchers.